Oikeusturva tahdosta riippumattomasta psykiatrisesta hoidosta päätettäessä - Valo, Janne (Helsinki Law Review, 2013)
In July 2012 the European Court of Human Rights (ECtHR) ruled in X v. Finland that the Finnish legislation regarding the involuntary treatment of psychiatric patients did not offer sufficient safeguards against arbitrary decisions in the light of the European Convention on Human Rights. The Court ruled that patients should be able to get an independent medical opinion, which the Finnish legislation did not guarantee. The Finnish Supreme Administrative Court in a subsequent en banc ruling disregarded the decision of the ECtHR and upheld a decision to place a patient in involuntary care even though the patient had not had the opportunity to get an independent opinion. The article takes a critical look at the decision of the Supreme Administrative Court and the following decisions by lower courts and their reasoning. The author’s conclusion is that the Court did not have grounds to disregard the earlier decision of the ECtHR and that its reasoning does not suffciently take into account the decision in question and the earlier praxis of the ECtHR.